An injectable double-crosslinking iodinated composite hydrogel as a potential radioprotective spacer with durable imaging function. Issue 15 (6th April 2021) - Wang, Cheng; Wu, Lingyun; Li, Wenxiang; Fei, Junhao; Xu, Jiaqi; Chen, Si; Yan, Senxiang; Wang, Xu
Abstract : Hydrogel spacers make prostate cancer radiotherapy safer and more effective. Abstract : Prostate cancer is one of the leading causes of cancer incidence among males worldwide. Radiotherapy can achieve similar oncological outcomes to those of radical prostatectomy. One concern is, however, radiation damage to the rectum because of the extreme proximity between the two organs. Inserting a biomaterial to separate the prostate and rectum is a promising strategy, and an injectable hydrogel is regarded to be the preferred spacer after screening of various materials. Nevertheless, there exist shortcomings for the currently available injectable hydrogel that cannot fully meet the unique requirements in clinical practice. In this work, a novel injectable hydrogel spacer based on carboxymethyl chitosan (CMC), aldehyde guar gum (AG), and aldehyde iohexol (DHQ) with an imaging function is fabricated. Contrast agent DHQ is chemically attached to CMC–AG network to form a double-crosslinking network to obtain a controlled degradation rate and high strength as well as durable CT imaging function. The hydrogel is injected subcutaneously into rats, where rapid gelation occurs and it serves as a hydrogel spacer. During the month-long in vivo studies, the spacer exhibits remarkable radiation dose attenuation and sustainable imaging function, as well as excellent toxicity profiles. This novel hydrogel shows excellent potential in the protection of critical organs during prostate cancer radiotherapy.